The Potential of Agricultural Waste Compost to Elevate Growth and Rice Production with the SRI Method in Acid Sulfate Soils - Saputra, Riza Adrianoor; Adhani, Muhammad Ridho; Sofyan, Antar; Jumar, Jumar (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2024)
Acid sulfate soil is a type of suboptimal wetland that has problems including high acidity, low nutrients, and high solubility of Al and Fe. These problems are often overcome by the use of lime and chemical fertilizers, but if we look closely, the unwise use of chemical fertilizers can have a negative impact on the land. The organic farming system through the System of Rice Intensification (SRI) can be an alternative solution for the development of rice cultivation in acid sulfate soils. Therefore, the application of organic matter in the form of compost from agricultural waste (rice straw, coffee grounds, and oyster mushroom baglog waste) is believed to be able to increase the growth and production of rice in acid sulfate soils. The purpose of this study was to determine the potential impact of agricultural waste compost on the growth and production of rice using the SRI method in acid sulfate soils. This research was carried out for six months, from March to September 2021, in Sungai Rangas Village, Martapura Barat District, Banjar Regency, South Kalimantan Province. This research method used a randomized block design (RBD) with 1 factor, namely the type of compost: a0 = without compost application, a1 = rice straw compost, a2 = coffee grounds compost, and a3 = oyster mushroom baglog waste compost. Each treatment consisted of five blocks, so there were 20 experimental units. The results showed that the application of agricultural waste compost has the potential to increase the growth and production of rice using the SRI method on acid sulfate soils. Rice straw compost (a1), coffee grounds compost (a2), and oyster mushroom baglog compost (a3) were able to increase plant height, number of productive tillers, weight of 1,000 grains of rice, and harvested dry grain weight compared to control (a0).